Effect of Lease Financing on the Financial Performance of Listed Consumer Goods Companies in Nigeria - Sani, Hafsat Muhammad; Abubakar, Halimatu Sa'adiya; Muhammad, Sulaiman Abubakar (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study examines the effect of lease financing on the performance of Listed Consumer Goods Companies in Nigeria. The ex-post factor research design was adopted with a sample of seven listed consumer goods companies who reported lease covering the period of implementation of IFRS 16, that is, from 2019-2022 was selected. Data were collected from secondary sources through the annual reports and accounts of the listed consumer goods companies in Nigeria. The study used pooled OLS (ordinary Leased Squares) to analyzed the data. The study used value of lease contract (right of use asset) to measure lease which is the independent variable and ROA as measure of financial performance. The findings showed that Lease finance showed a negative but significant effect on ROA of consumer goods companies in Nigeria. The study therefore recommends that Consumer goods companies should focus on improving their lease management practices to ensure efficient utilization of leased assets. This may involve implementing robust tracking systems, optimizing lease terms, and renegotiating lease agreements where necessary to better align with business objectives as it has shown negative effect on financial performance.